Primary Health Service Efforts To Reduce Stunting In Children In Coastal Areas - Hidaya, Nurman; Hartika, Andi Yuniarsy; Sinta, Mezu Tri (Universitas Muhammadiyah Surakarta, 2025)
Background: The condition of stunting must be treated seriously, considering that stunting has an impact on disrupting cognitive, motor and verbal development in children. Community Health Centers (Puskesmas), as a type of first-level health-service-facility, have an important role in the national health system, especially the health-effort-subsystem. The aim of the research is to understand the strategies and actions of community health centers in reducing stunting among children. Methods: Qualitative research with a phenomenological design involving 11 participants with in-depth interviews was used to collect data, which was then analyzed using Braun & Clark's theme framework Results: According to the research findings, there are 4 main themes that describe the role of primary health services at community health centers in reducing stunting in children, including: 1. Revalidation of Stunting Rates in Children 2. Providing Education 3. Cross-sector Collaboration and 4. Providing Supplemental Food. Conclusion: It is hoped that there will be training to increase the competency of health cadres, and the role and cooperation of all components in reducing stunting in children.